Mangrove PEMETAAN MANGROVE DALAM BENTUK WEBGIS (STUDI KASUS : MUARA GEMBONG) - Fawaz Fawaz (Universitas Ivet, 2021)
Muara Gembong is one of the areas located in Bekasi Regency, West Java which has a huge mangrove potential and spread on its coast. But in reality the mangrove forest in Muara Gembong is degraded from year to year. In order to know how much of the impact of degradation caused by residential land, cultiva-tion ponds are needed mapping first to further overcome the problem. The most appropriate way to map the process is to use remote sensing and webgis. The purpose of this study is to produce applications in the form of mangrove mapping webgis that users can access in internet browsers with pages (www.upi.asia). Using mangrove mapping websites can display maps of bekasi city areas and mangrove mapping over the internet without the need for the help of GIS applications. This application can display information about mangrove mapping, bekasi city mapping, information about the makers of mangroves, information to zoom the entire city of Bekasi, information about legends available, can also download bekasi maps and mangrove mapping for free and literature menu in the form of blogs so that users know general information about mangroves. Webgis creation uses several methods and applications such as utilization of the Google Maps API. Utilization of Leaflet.js, utilization of CodeIgniter and utilization of MySQL as a form of database. To do the mapping process used latitude and longitude information based on Google Maps, this serves to facilitate coding in the webgis creation process. The app was successfully run using either a computer or smartphone, and tested the stability of 10 respondents who discussed the effectiveness of the application, user ease and user satisfaction. Based on the results of questionnaires that have been done, mangrove mapping webgis application is quite effective and easy to use by users.